MPEG-Past and Future - Leonardo Chiariglione (CSELT; Italy) (Tongxin xuebao)
The dream of digital audio and video and,of late,multimedia information freely accessible to human beings through a variety of delivery media is getting real thanks to the availability of the standard MPEG technology to compress audio-visual information and progress in signal processing techniques to digitise currently analogue delivery media. The paper gives a comprehensivereport on the philosophy behind and the activity of the MPEG committee in the development of the MPEG-1 and MPEG-2 standards.The current activity to develop an entirely new standard for the coded representation of audio-visual information providing new functionalities is also included.